Integrated physical and mental management for China’s elderly: insights from Long-gang District, Shenzhen - Wang, Xun qiang; Yang, Ce ce; Sun, Xi ling (Frontiers in Aging, 2024)
China is in a period of rapid population aging. The total population of the elderly aged 60 and above in mainland China was 264 million in 2020, and is the country with the largest elderly population in the world, which is home to 1/5 of the world's older people. The urgency of actively coping with the aging population has never been greater, and China has raised it to the height of national strategy. To this end, China has issued several plans and projects on aging work. Many of them include multiple overlapping components. The management of physical illness and mental illness in the elderly is over-differentiated and segmented. However, it is common for older adults with complex health problems. The body and mind are inherently integrated and interact with each other, and should not be separated. There is an urgent need for integrated healthcare services for the physical and mental health of the elderly population. The national basic public health services play an important role in early detection and awareness of health problems for the elderly in community health services. This paper introduces the elderly health management services, one of the national basic public health projects, and the psychological care project for the elderly in Shenzhen, Guangdong Province, China. Taking Long-gang District's exploration of the joint management of physical and mental health of the elderly as an example, this review discusses the difficulties of the elderly health work, and the feasibility of integrating the elderly mental health and physical health in medical care.We outlook to build an integrated platform for physical and mental health of the elderly in China. Focus on the needs of older population, strengthen community health services, build a integrative team, fully publicize and improve health literacy of the elderly, link up and down and work together, improve coordination between providers of medical care and social services. It is of great significance to construct a strong public health system for the elderly and promote the realization of the grand goal of Healthy China.